2006
DOI: 10.1080/10473289.2006.10464462
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of Instrumentation for the Semicontinuous Determination of Particulate Nitrate (and Other Water-Soluble Particulate Components)

Abstract: Studies conducted at the U.S. Environmental Protection Agency facility in Research Triangle Park, NC, and at a field study in Southern California have demonstrated the capability for the semicontinuous determination of particulate nitrate (and other water-soluble ionic species). Two instruments, an R&P Series 8400N Ambient Particulate Nitrate Monitor (8400N) and an ion chromatography (IC)-based prototype monitor developed at Texas Tech University, were evaluated both in the laboratory using aqueous standards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Comparable underprediction of the 8400N as compared to other measurement techniques (noted as the slope in Table 2) has been cited previously at various US urban and rural centers Wittig et al, 2004;Grover et al, 2006;Long and McClenny, 2006;Rattigan et al, 2006). A summary of in- strument intercomparison relationships is presented in Table 2 where all centres were urban environments with the exception of Whiteface Mountain, NY.…”
Section: Semi-continuous Inter-instrument Comparisonmentioning
confidence: 52%
See 3 more Smart Citations
“…Comparable underprediction of the 8400N as compared to other measurement techniques (noted as the slope in Table 2) has been cited previously at various US urban and rural centers Wittig et al, 2004;Grover et al, 2006;Long and McClenny, 2006;Rattigan et al, 2006). A summary of in- strument intercomparison relationships is presented in Table 2 where all centres were urban environments with the exception of Whiteface Mountain, NY.…”
Section: Semi-continuous Inter-instrument Comparisonmentioning
confidence: 52%
“…Low efficiency may have resulted in incomplete NO 2 to NO conversion causing nitrate measurement underestimations. It is also worth noting that Long and McClenny (2006) observed only a negative bias with the 8400N as compared to the GPIC during ambient sampling; the 8400N accurately measured high nitrate concentrations when operating under controlled laboratory conditions. These results suggested that interfering species may have contributed to the divergence between measurement techniques at high nitrate concentrations.…”
Section: Semi-continuous Inter-instrument Comparisonmentioning
confidence: 86%
See 2 more Smart Citations
“…The most significant differences were observed during a persistent inversion at the beginning of the sampling period, which was associated with ground level fog and high humidity. Incomplete flash volatilization by the R&P Nitrate Monitor under conditions of high humidity (Long and McClenny 2006) may explain the differences observed between the two monitoring techniques. Unfortunately, PC-BOSS data were not obtained during this time period of the sampling campaign.…”
Section: Inorganic Constituent Measurementsmentioning
confidence: 92%